Differences between Homicides Committed by Lone and Multiple Offenders in Korea. Issue 1 (16th May 2018) - Park, Jisun; Cho, Joon Tag
Abstract: The aim of this study was to differentiate between homicides committed by multiple offenders and homicides committed by lone offenders. Using data on homicide incidents that occurred in South Korea between 1985 and 2008, we compared 134 homicides committed by multiple offenders, with 369 homicides committed by lone offenders. A greater proportion of homicides committed by multiple offenders involved injuries to the victim's head compared to homicides by lone offenders. Homicides committed by multiple offenders were more likely to involve blunt instruments and ligatures, whereas homicides by lone offenders were more likely to involve sharp instruments. In addition, a majority of the homicides committed by multiple offenders were planned. The results of this study have practical implications for homicide investigations, as well as theoretical implications for homicide research on the difference in offense behaviors based on the number of offenders.